2021
DOI: 10.1111/gcb.15938
|View full text |Cite
|
Sign up to set email alerts
|

Temperature acclimation of leaf respiration differs between marsh and mangrove vegetation in a coastal wetland ecotone

Abstract: Temperature acclimation of leaf respiration (R) is an important determinant of ecosystem responses to temperature and the magnitude of temperature‐CO2 feedbacks as climate warms. Yet, the extent to which temperature acclimation of R exhibits a common pattern across different growth conditions, ecosystems, and plant functional types remains unclear. Here, we measured the short‐term temperature response of R at six time points over a 10‐month period in two coastal wetland species (Avicennia germinans [C3 mangrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 86 publications
(126 reference statements)
1
6
0
Order By: Relevance
“…It has been hypothesized that C 4 species are less capable of thermal acclimation than C 3 species (Yamori et al, 2014). However, C 4 plants sometimes show equivalent acclimation responses to warming (Sturchio et al, 2021; Yamori et al, 2014). Our results are similar to those of Dwyer et al (2007) who found slight positive effects of warming on photosynthetic rates of three C 4 species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that C 4 species are less capable of thermal acclimation than C 3 species (Yamori et al, 2014). However, C 4 plants sometimes show equivalent acclimation responses to warming (Sturchio et al, 2021; Yamori et al, 2014). Our results are similar to those of Dwyer et al (2007) who found slight positive effects of warming on photosynthetic rates of three C 4 species.…”
Section: Discussionmentioning
confidence: 99%
“…This, and decreased net primary production observed during elevated regional summer temperatures (Noyce et al, 2019), indicates that moderate amounts of warming in the region are likely elevating temperatures closer to or above this metabolic optimum. Although some studies have indicated that marsh grasses can acclimate leaf respiration and photosynthetic capacity to increasing temperatures (Sturchio et al, 2021;Wang et al, 2020), the warmest treatment likely exceeds the metabolic temperature optimum during warm summer days leading to a reduction in marsh elevation, analogous to the hump-shaped relationships between temperature and productivity proposed for S. alterniflora more globally (Liu et al, 2016(Liu et al, , 2020Rogers et al, 2006;Więski & Pennings, 2014). Our observations of consistent treatment optima, where root production, elevation change, and carbon accumulation rates in two disparate plant communities were maximized at +1.7°C, suggest that the qualitative patterns are applicable beyond our particular study area, but that the exact temperature optimum may vary around +1.7°C (Figure 1c).…”
Section: Moderate Warming Optimizes Marsh Resilience and Carbon Accum...mentioning
confidence: 99%
“…Positive responses of C 4 species to warming have been observed in many studies (e.g., [ 58 , 61 ]). However, both C 3 and C 4 plants have been found to have similar photosynthetic responses to warming [ 63 , 64 ], and inhibition of C 4 plants may appear with a high temperature or a combination of warming and water deficit [ 42 , 58 ]. Thus, a concurrence of warming and drought jointly presenting severe abiotic stress could largely constrain the photosynthetic performance of either C 3 or C 4 species, especially in a xeric area [ 42 , 58 ].…”
Section: Discussionmentioning
confidence: 99%